INTEGRATING THE MONOTHEISM VALUE IN SCIENCE LEARNING USING THE "SA'ADAH" METHOD IN MI UNGGULAN NURIS JEMBER - Siti Hamidahtur Rofi’ah; Mohammad Misbahul Munir; Wildania Unsika (International Conference on Humanity Education and Society (ICHES), 2024)
The current phenomenon is that religion and science are separated from each other, if this continues to develop then what will happen is that there is a dichotomy of science so that a person will only be intellectually intelligent, he does not know God and the role of science is solely for practical purposes.The existence of a dichotomy between religious knowledge and science makes a person only intellectually intelligent, he does not know his God. Therefore it is necessary to inculcate religious values in learning general sciences including science, so that religion and science can go hand in hand. MI Unggulan Nuris Jember has a vision, mission and commitment to become an educational institution that seeks to integrate Islamic values in all aspects of student life in the school environment both intracurricularly and extracurricularly. This can be observed in learning activities that lead to an increase in the spiritual intelligence of students in science subjects. This study used a qualitative approach. This type of case study, data collection techniques in this study were carried out by several means of observation, interviews and documentation. Researchers used data analysis which was carried out interactively. According to Miles, Huberman, and Saldana, data analysis that is carried out interactively must go through a process of condensing data, presenting data and drawing conclusions. The validity of the data in this study used source triangulation and method triangulation. The results of the study show that MI Unggulan Nuris Jember uses the Sa'adah method (Sam'ah, Absoro and Af'idah) as a method of integrating the values of monotheism in science learning which is embodied in the vision, mission and madrasa program as well as the religious culture of the madrasa. At the operational level, the teacher integrates the value of monotheism in the Learning Implementation Plan. There are facilities and infrastructure such as mosques, labs and libraries that support the integration of monotheistic values in learning. The learning method used in integrating the value of monotheism in science learning uses lecture, discussion, question and answer, experiment and Tadabbur Alam methods.